Perbandingan Response Time Penggunaan Index, Views, dan Materialized Views Database Mysql - Witono, Edi; Parno, P (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The existence of information technology today can help the government in carrying out the task of providing services to the public that are efficient and transparent. One of them is the SisfoSPM application used by the Badan Litbang unit of the Ministry of Education and Culture's National Education and Culture Agency to verify spending budgets in the use of the State Revenue and Expenditure Budget. This web-based application has been using Mysql as its database since 2017. The amount of data from each year, makes this application run slowly, especially related to queries that display log data verification results of each employee. This study used experimental methods with employee log transaction data from 2017-2021 amounting to 780,212 records. The study uses three stages: preparation, experimentation and analysis of results. The results of this research, obtained the results of the main response time query module sisfoSPM application employee log calculation with the amount of data as much as 780,212 using the index method for 1.95 seconds, using the views method for 1.85 seconds and using the materialized views method for 0.01 seconds. With these results, researchers can draw the conclusion that the use of materialized views provides the fastest response time results